Becoming a Psychotherapist: Learning Practices and Identity Construction Across Communities of Practice - Alby, Francesca; Zucchermaglio, Cristina; Fatigante, Marilena (Frontiers in Psychology, 2022)
Within a perspective that views groups as communities of practice and sites of construction of knowledge, learning, and identity, this article aims to explore the contribution that participation in different groups over the course of one’s life provides to the development of the professional practices of psychotherapist trainees enrolled in the C.O.I.R.A.G. school, an Italian graduate program in group psychotherapy. Through qualitative analyses of 10 semi-structured interviews, our study empirically shows that by participating in groups, the trainees not only learn the practices of that group but also develop a sort of meta-learning which takes place across groups. The results highlight that: (1) Transversality, duration, and informality are found to be the group properties with the highest formative value; and (2) Learning practices across different groups have common characteristics: are organized around complex topics of group life (e.g., how to manage conflicts, how to join and leave groups, etc.), began in early group experiences, are in continuous evolution, are associated with a critical event, and a negative affect. At the same time, it seems that these critical events are exactly what triggered and sustained the learning practices. Data from the interviews also showed how professional identities are constructed as the outcome of learning in different communities of practice. The study outlines how the experience made in different groups is elaborated in and through meaningful self-narratives, highlighting them as a fundamentally collective and culturally shaped sense-making process. Overall, these results contribute to a better understanding of learning processes as situated and jointly constructed through multiple group participations over time. Furthermore, they contribute to highlighting the role of self-narratives as a primary way through which trainees shape their identity as self-reflexive professionals who are competent in reading group dynamics. Directions for future research and suggestions for psychotherapist training paths are outlined in the conclusions.